Comorbidities in patients over 60 years of age treated at the rehabilitation clinic - Pietrzyńska, Magdalena; Stawińska-Witoszyńska, Barbara; Krzyżaniak, Alicja; Łańczak-Trzaskowska, Magdalena; Nowak, Kamila (Anthropological Review, 2015)
Patients aged above 60 represent a very diversified population group with respect to their health condition. This may result from multimorbidity. In the rehabilitation process of elderly patients it is especially crucial to identify not only the underlying diseases which constituted the grounds for referral to the rehabilitation clinic, but also the comorbidities that have to be taken into consideration while planning their rehabilitation. The aim of the present paper is the assessment of comorbidities in patients of the rehabilitation clinic. The study population included 1616 patients (447 man and 1169 women) treated at the rehabilitation clinic. The factors put through analysis were the age and gender of the patient, the main diagnosed (underlying) illness subject to rehabilitation treatment, as well as comorbidities. All diseases, both the underlying conditions and the comorbidities have been classified according to the International Statistical Classification of Diseases and Related Health Problems (10th revised edition). The main reasons for the treatment at the rehabilitation outpatient clinic were arthrosis of the spine, knee and hip joints, polyarthritis, osteoporosis, diseases of the central nervous system diseases and paralytic syndromes as consequences of strokes, hypertension or atherosclerosis, as well as post-traumatic conditions. The most frequent comorbidities occurring in patients of the rehabilitation clinic were cardiovascular diseases (irrespective of the age group and the underlying disease). In the age group of 60–64, the subsequent comorbidities were gastrointestinal and cancers, and in the age of 65–74, neoplasms were the most frequently occurring comorbidities. The performed analysis resulted in the following conclusions: The majority of patients diagnosed and treated at the rehabilitation centre suffered from irregularities in the muscular, articular and skeletal system or the connective tissue (those were mainly the arthrosis of the spine, hip and knee joints as well as osteoporosis). The most frequently observed comorbidities in patients of the rehabilitation clinic were cardiovascular and gastrointestinal diseases, as well as neoplasms.